Why pediatricians need to know the disorders of sex development: experience of 709 cases in a specialized service - Mayra de Souza El Beck; Carlos W. Germano; Beatriz A. Barros; Juliana G.R. Andrade; Guilherme Guaragna‐Filho; Georgette B. Paula; Márcio L. Miranda; Mara S. Guaragna; Helena Fabbri‐Scallet; Tais N. Mazzola; Nilma L. Viguetti‐Campos; Társis A.P. Vieira; et al. (Brazilian Society of Pediatrics, 2020)
Objective: To evaluate, in a sample of patients with disorders of sex development (DSD), data related to the age at referral and their correlation with the initial complaints, gender at referral, defined gender after diagnosis and etiological diagnosis. Methods: Retrospective review of the age at the first consultation and the reason for it, initial social gender and gender after the diagnosis, karyotype and etiological diagnosis of all cases treated at a DSD outpatient clinic between 1989 and 2016. Cases that did not involve DSD and DSD diagnoses that do not usually involve ambiguous genitalia, thus not requiring specialized monitoring, were excluded. Results: Of the 1793 treated cases, 1139 were diagnosed with some type of DSD. This study excluded 430 cases (272 with Turner's syndrome, 66 with Klinefelter syndrome, and 92 with pure gonadal dysgenesis), thus a total 709 individuals were included. Of these, 82.9% were referred due to ambiguous genitalia; only one‐quarter were still in the first month of life, and 6.6% were referred due to pubertal delay, with most of them aged 10 years or older. Of these patients, 68.6% had a diagnosis of XY DSD, 22.4% of XX DSD, and 9% of sex chromosome abnormalities. Conclusions: This study presents the largest series in the literature of patients with DSD treated in a single center. The time of referral of the majority of patients with ambiguous genitalia fell short of the ideal, and milder cases of ambiguous genitalia and many with pubertal manifestations were referred even later. The results reinforce the importance of continuing education for professionals who will have the first contact with these patients, mainly pediatricians and neonatologists. Resumo: Objetivo: Avaliar em uma amostra de pacientes com distúrbios da diferenciação do sexo (DDS), dados relacionados à idade, ao encaminhamento e sua correlação com as queixas iniciais, ao sexo ao encaminhamento e ao sexo final e diagnóstico etiológico. Métodos: Revisão retrospectiva da idade por ocasião da primeira consulta e motivo dela, sexo social inicial e após definição do diagnóstico, cariótipo e diagnóstico etiológico de todos os casos atendidos em um ambulatório especializado em DDS entre 1989 e 2016. Foram excluídos casos que não compreendiam DDS e diagnósticos de DDS que não cursam comumente com ambiguidade genital, não necessitam de acompanhamento especializado. Resultados: Dos 1.793 casos atendidos, 1.139 foram diagnosticados com algum DDS. Excluíram‐se 430 (272 síndrome de Turner, 66 síndrome de Klinefelter e 92 disgenesia gonadal pura), totalizando 709. Desses, 82,9% foram encaminhados por ambiguidade genital, somente um quarto ainda no primeiro mês de vida e 6,6% por atraso puberal, a maioria com 10 anos ou mais; 68,6% tiveram diagnóstico de DDS XY; 22,4% DDS XX e 9% de anomalias dos cromossomos sexuais. Conclusões: Este estudo apresenta a maior casuística na literatura de pacientes com DDS atendidos em um único serviço. O momento de encaminhamento da maioria dos pacientes com ambiguidade genital foi aquém do ideal e casos mais leves de ambiguidade e muitos com manifestações puberais foram encaminhados ainda mais tardiamente. Os resultados reforçam a importância do ensino continuado a profissionais que terão o primeiro contato com esses pacientes, principalmente pediatras e neonatologistas.